Giacinto Scelsi - homo viator and his musical itinerary - Skupin, Renata (Interdisciplinary Studies in Musicology, 2018)
Giacinto Scelsi was a “traveller to the East”, who tied his life inextricably to creative work. As a composer, he sought a path for the renewal of his own musical language, shaped during his youth under the powerful influence of other composers’ styles. On becoming a homo religiosus, in the Eliadean sense, he found his own path to transcendence through art (creation), deeply inspired by those great traditions of the Orient in which art was a reflection of the artist’s spirituality. The topos of the path is one of the main keys to interpreting Scelsi’s work. His works for large orchestra and choir contain distinct traces of a Scelsian “voyage to the East”. They form one great cycle, integrated by the motif of the path, expressed through meanings added in the content of the individual programme-titles. The cycle’s finale, the eschatological Pfhat (1974), is the musical depiction of a journey that ends with “a clear, primordial light,” symbolising man’s encounter with a higher reality and “great liberation” as the goal of his spiritual path. The chronotope of the path is revealed in the very musical material of his orchestral works: in their quasi-visual soundspace. It is manifest, among other things, in the processual form - one might even say the storyline - and the consistently applied procedure of transforming sonorities, texture and rhythmic structures. A fundamental symbolic function is discharged by various forms of “upwards path”, linked to the dramaturgical role of an upwards motion pattern in the melody and an upwards movement in the tonal-harmonic plan of the orchestral works. The most crucial of all the variants of the motif of the path is the direction “into the core”, that is, towards the “inner space” of the sound. This carries significance both in the dimension of the harmonic spectrum of a sound and also its spiritual depth - the mystical dimension. The journey to the centre acquires the status of an emblematic topos of the Scelsian poetic of the viaggio al centro del suono [journey to the centre of the sound].